A comprehensive model for energy management strategies in coordination with manufacturing and organization strategies and its effect on energy management performance - Naghmeh Khabazi Kenari; Naser Feghhi Farahmand; Soleyman Iranzadeh (Cogent Business & Management, 2018)
Today, energy management is an important tool for organizations to achieve their key goals, but only by considering the role of energy management strategies, we cannot achieve scientific and precise results from energy management system. So this research aims to propose a comprehensive model of energy management strategies that is in line with organization and manufacturing strategies and increases performance of energy management. In this research, we collect information from the petrochemical companies and refineries, whose energy intensity is determined by hydrocarbon balance sheet of the country and examine them. Results show that organizations in which the type of their energy management, manufacturing, and organization strategies are coordinated have better energy management performance.
Keywords: 650